Van der Waals nano-thermistor - He, Yanchao (Nanyang Technological University, 2023)
Temperature is a fundamental thermodynamic variable, an essential part of science, and a key factor in technology. Therefore, it is important to develop a detection system with ultrahigh spatial and temperature resolution for various applications such as biomedicine, extreme ultraviolet (EUV) lithography, and micro/nano-electronics. Negative temperature coefficient resistance (NTCR) thermistor, as a promising candidate that can provide ultrahigh temperature resolution, has acquired enormous commercial success, but improvements, especially in spatial resolution, remain a great challenge. Herein, we present a series of layered metal phosphorous trichalcogenides (MPTs). These compounds exhibit distinctive material properties that position them as promising candidates for temperature sensing applications. Notably, the unique cation instability inherent to these Van der Waals (vdW) materials facilitates small polaron conduction, resulting in Arrhenius-type temperature-dependent conductivity that adheres to NTCR behavior. We showcase nano-thermistors boasting nanometric lateral resolution and an impressive accuracy of 0.1 K. Moreover, we demonstrate real-time, precise temperature monitoring for heat sources spanning microscale to nanoscale dimensions and across homojunctions and heterojunctions. This study stands to chart a path towards the advancement of next generation temperature sensing technology.